Natural food flavors and colorants - Attokaran, Mathew; Wiley InterScience (Online service) (Hoboken, N.J. : Wiley, 2011)
"Natural Extracts as Food Flavors and Colorants, as its name implies, describes the natural extracts that are used as food flavors and colors. Part I addresses techniques and general characteristics of these natural extracts, including essential oils; solvent extraction; food colors; dispersion and solubitization; effect of heat; nutraceutical function; organoleptic function; and regulatory and analytical aspects. Part II focuses on each individual natural extract, with coverage including raw material; chemistry; extraction specifics; methods of testing; and uses. Chemical structure and properties of key constituents are provided. Wherever available, CAS number, FEMA number and E number are given. Determination of principal and significant constituents is described, so as to help analysts choose the right methods. Food scientists, researchers and product development professionals alike will find Natural Extracts as Food Flavors and Colorants an invaluable resource for understanding and using these natural food ingredients."--
Machine generated contents note: Preface -- Part I General -- Chapter -- 1. Analytical matters -- 2. Flavours -- 3. Spices -- 4. Essential oils -- 5. Food colours -- 6. Preparation of plant material for extraction -- 7. Methods of extraction of essential oils -- 8. Solvent extraction -- 9. Super critical fluid extraction -- 10. Homogenization of extracts -- 11. Suspension on solids -- 12. Deterioration during storage and processing -- Part IIIndividual items -- 13. Ajwain (Bishop's weed) -- 14. Anka-red fungus -- 15. Aniseed -- 16. Annatto -- 17. Asafoetida -- 18. Basil -- 19. Bay leaf -- 20. Beet root -- 21. Bergamot mint -- 22. Black cumin -- 23. Black pepper -- 24. Capsicum -- 25. Carab pod -- 26. Caramel -- 27. Caraway -- 28. Cardamom -- 29. Carrot -- 30. Cassia -- 31. Celery seed -- 32. Chicory -- 33. Cinnamon -- 34. Cinnamon leaf -- 35. Clove -- 36. Clove leaf -- 37. Coca leaf -- 38. Cochineal -- 39. Cocoa -- 40. Coffee -- 41. Coriander -- 42. Coriander leaf -- 43. Cumin -- 44. Curry leaf -- 45. Date -- 46. Davana -- 47. Dill -- 48. Fennel -- 49. Fenugreek -- 50. Galangal-Greater -- 51. Galangal-Kaempferia -- 52. Galangal-Lesser -- 53. Garcinia fruit -- 54. Garlic -- 55. Ginger -- 56. Grape -- 57. Grape fruit -- 58. Green leaves -- 59. Hops -- 60. Hyssop -- 61. Japanese mint -- 62. Juniper berry -- 63. Kokam -- 64. Kola nut -- 65. Large cardamom -- 66. Lemon -- 67. Lemongrass -- 68. Licorice -- 69. Lime -- 70. Lovage -- 71. Mace -- 72. Mandarin -- 73. Marigold -- 74. Marjoram -- 75. Mustard -- 76. Nutmeg -- 77. Onion -- 78. Orange -- 79. Oregano -- 80. Paprika -- 81. Parsley -- 82. Pepper long -- 83. Peppermint -- 84. Pimenta -- 85. Red sandalwood -- 86. Rosemary -- 87. Saffron -- 88. Sage -- 89. Savory (Sweet summer) -- 90. Spearmint -- 91. Star anise -- 92. Sweet flag (Calamus) -- 93. Tamarind -- 94. Tarragon -- 95. Tea -- 96. Thyme -- 97. Tomato -- 98. Turmeric -- 99. Vanilla -- Part III Future needs -- 100. Opportunities in natural flavours -- 101. Opportunities in natural colorants.
Includes bibliographical references and index.
Print version record.
Keywords: Flavoring essences; Coloring matter in food; Natural foods; Natural food; Chemical engineering; Engineering; TECHNOLOGY & ENGINEERING -- Food Science; Coloring matter in food; Flavoring essences; Natural foods; Electronic books